Effect of metal species on the stability of Me-N-C catalysts during accelerated stress tests mimicking the start-up and shut-down conditions. (20th July 2017) - Martinaiou, Ioanna; Shahraei, Ali; Grimm, Fabian; Zhang, Hongbin; Wittich, Carolin; Klemenz, Sebastian; Dolique, Stephanie J.; Kleebe, Hans-Joachim; Stark, Robert W.; Kramm, Ulrike I.
Graphical abstract: Highlights: Comprehensive study of the influence of metal species in Me-N-C on the degradation during accelerated stress tests. Comparison of all data indicate the importance of the D3 band for the activity and stability of Me-N-C catalysts. The displacement of the metal out of the N4 plane has a strong impact on the stability of Me-N-C catalysts. A model for the degradation of Me-N-C catalysts during start-up and shut down conditions is proposed. Abstract: Currently, Me-N-C catalysts are the most prominent alternative to Pt/C catalysts for the oxygen reduction reaction in acidic media. It is well known that the achievable activity and selectivity strongly correlates with the nature of metal species. However, so far the effect of the metal species on the stability of these catalysts was not investigated systematically. In this work, a group of 13 different Me-N-C catalysts were investigated with respect to their activity and stability in accelerated stress tests mimicking the start-up and shut-down conditions (AST_SSC). A strong correlation between the nitrogen content assigned to different MeN4 sites and the D3 band from Raman spectroscopy is found. Moreover, we were able to correlate changes in the D3 band and variations in the displacement of the metal atoms out of the N4 plane with the losses in ORR activity. Based on these findings, we propose a model for the degradation of Me-N-C catalysts during accelerated stress tests mimicking the start-up and shut-down conditions.